Application of practice-based learning in graph theory - Saputro, Marhadi; Prihatin, Iwit (SAINTIS Publishing, 2023)
Learning graph theory is an important topic in the world of mathematics and computer science. However, students often face difficulties in understanding the concepts and practical application of graph theory. Therefore, this study aims to apply practicum-based learning methods in teaching graph theory to students. The method used in this study involves the application of practical work through the use of maple. Students are given the opportunity to interactively run experiments, analyze results, and relate them to graph theory concepts. Apart from that, they are also given assignments that focus on the practical application of graph theory in real-world contexts. This research was conducted on students of the Mathematics Education Study Program IKIP PGRI Pontianak, totaling 1 class using an experimental approach. The collected data were analyzed quantitatively to evaluate the effectiveness of practicum-based learning methods in increasing students' understanding of graph theory. The results of the study show that the application of practicum-based learning in graph theory has a positive impact on student understanding. Students show a significant increase in their understanding of graph theory concepts and their ability to apply the theory to real-world situations. In addition, students also provide positive feedback regarding interactive and fun learning experiences.